ANALYSIS HYDROLITHOSPHERE PROCESSES OF THE CONTROL OBJECT KISLOVODSK FIELD OF MEDICAL CARBON DIOXIDE MINERAL WATERS - George Alexandrovich Shchedrin (Современная наука и инновации)
The article describes the analysis hydrolithosphere processes of the control object Kislovodsk medical field acidulous waters with the aim of developing and establishing management systems hydrolithosphere processes.